Point-of-care ultrasound-guided regional anaesthesia in older ED patients with hip fractures: a study to test the feasibility of a training programme and time needed to complete nerve blocks by ED physicians after training. Issue 7 (5th July 2021) - Lee, Jacques Simon; Bhandari, Tina; Simard, Robert; Emond, Marcel; Topping, Claude; Woo, Michael; Perry, Jeffrey; Eagles, Debra; McRae, Andrew D; Lang, Eddy; Wong, Charles; Sivilotti, Marco; et al.
Abstract : Objectives: Point-of-care ultrasound-guided regional anaesthesia (POCUS-GRA) provides safe, rapid analgesia for older people with hip fractures but is rarely performed in the emergency department (ED). Self-perceived inadequate training and time to perform POCUS-GRA are the two most important barriers. Our objective is to assess the feasibility of a proposed multicentre, stepped-wedge cluster randomised clinical trial (RCT) to assess the impact of a knowledge-to-practice (KTP) intervention on delirium. Design: Open-label feasibility study. Setting: An academic tertiary care Canadian ED (annual visits 60 000). Participants: Emergency physicians working at least one ED shift per week, excluding those already performing POCUS-GRA more than four times per year. Intervention: A KTP intervention, including 2-hour structured training sessions with procedure bundle and email reminders. Primary and secondary outcome measures: The primary feasibility outcome is the proportion of eligible physicians that completed training and subsequently performed POCUS-GRA. Secondary outcome is the time needed to complete POCUS-GRA. We also test the feasibility of the enrolment, consent and randomisation processes for the future stepped-wedge cluster RCT (NCT02892968 ). Results: Of 36 emergency physicians, 4 (12%) were excluded or declined participation. All remaining 32 emergency physicians completed training and 31 subsequently treated at least one eligible patient. Collectively, 27/31 (87.1%) performed 102 POCUS-GRA blocks (range 1–20 blocks per physician). The median (IQR) time to perform blocks was 15 (10–20) min, and reduction in pain was 6/10 (3–7) following POCUS-GRA. There were no reported complications. Conclusion: Our KTP intervention, consent process and randomisation were feasible. The time to perform POCUS-GRA rarely exceeded 30 min, Our findings reinforce the existing data on the safety and effectiveness of POCUS-GRA, mitigate perceived barriers to more widespread adoption and demonstrate the feasibility of trialling this intervention for the proposed stepped-wedge cluster RCT. Trial registration number: Clinicaltrials.gov #02892968